Sintesis trigliserida rantai menengah melalui transesterifikasi gliserol dan asam-asam lemaknya - Tirto Prakoso; Sarastri Cintya Hapsari; Pilanda Lembono; Tatang H. Soerawidjaja (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2006)
Medium Chain Trigliceride (MCT) is a fat substitution which actually is an ester ofmedium ringfatty acid (C, - C,) from glycerol. MCT is not naturally available, so that MCT synthesis is needed. Hartman eta/ (1989) made MCT throught esterification with and without catalyst Zn and do the finishing of MCT product using vacum destilation. This study consisted of the application of Hartman's method to bring the esterification reaction with and without catalyst. The esterification reaction without catalyst performed at I70